Transcriptional Changes in Dorsal Spinal Cord Persist after Surgical Incision Despite Preemptive Analgesia with Peripheral Resiniferatoxin. (March 2018) - Raithel, Stephen J.; Sapio, Matthew R.; LaPaglia, Danielle M.; Iadarola, Michael J.; Mannes, Andrew J.
Abstract : Background: Peripheral nociceptors expressing the ion channel transient receptor potential cation channel, subfamily V, member 1, play an important role in mediating postoperative pain. Signaling from these nociceptors in the peri- and postoperative period can lead to plastic changes in the spinal cord and, when controlled, can yield analgesia. The transcriptomic changes in the dorsal spinal cord after surgery, and potential coupling to transient receptor potential cation channel, subfamily V, member 1–positive nociceptor signaling, remain poorly studied. Methods: Resiniferatoxin was injected subcutaneously into rat hind paw several minutes before surgical incision to inactivate transient receptor potential cation channel, subfamily V, member 1–positive nerve terminals. The effects of resiniferatoxin on postincisional measures of pain were assessed through postoperative day 10 (n = 51). Transcriptomic changes in the dorsal spinal cord, with and without peripheral transient receptor potential cation channel, subfamily V, member 1–positive nerve terminal inactivation, were assessed by RNA sequencing (n = 22). Results: Peripherally administered resiniferatoxin increased thermal withdrawal latency by at least twofold through postoperative day 4, increased mechanical withdrawal threshold by at least sevenfold through postoperative day 2, and decreased guarding score by 90% relative to vehicle control ( P < 0.05). Surgical incision induced 70 genes in the dorsal horn, and these changes were specific to the ipsilateral dorsal horn. Gene induction with surgical incision persisted despite robust analgesia from resiniferatoxin pretreatment. Many of the genes induced were related to microglial activation, such as Cd11b and Iba1. Conclusions: A single subcutaneous injection of resiniferatoxin before incision attenuated both evoked and nonevoked measures of postoperative pain. Surgical incision induced transcriptomic changes in the dorsal horn that persisted despite analgesia with resiniferatoxin, suggesting that postsurgical pain signals can be blocked without preventing transcription changes in the dorsal horn. Abstract : Using a rat model of postsurgical pain, it was shown that a single localized injection of resiniferatoxin reduced evoked and nonevoked pain-related behaviors over the entire period of postoperative recovery. Analysis of spinal cord dorsal horn tissue revealed that resiniferatoxin pretreatment did not block most changes in gene expression, including the expression of genes associated with microglia, despite reducing pain-related behaviors.Supplemental Digital Content is available in the text.